2018
DOI: 10.3390/su10124526
|View full text |Cite
|
Sign up to set email alerts
|

Forest Landscape Change and Preliminary Study on Its Driving Forces in Ślęża Landscape Park (Southwestern Poland) in 1883–2013

Abstract: Changes in forest landscapes have been connected with human activity for centuries and can be considered one of the main driving forces of change from a global perspective. The spatial distribution of forests changes along with the geopolitical situation, demographic changes, intensification of agriculture, urbanization, or changes in land use policy. However, due to the limited availability of historical data, the driving forces of changes in forest landscapes are most often considered in relation to recent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 56 publications
(74 reference statements)
1
42
0
Order By: Relevance
“…Accordingly, understanding change processes of landscape and influencing factors, namely biophysical and anthropogenic, has become a priority for researchers, managers, and decision makers [4][5][6][7]. In this regard, population growth as an anthropogenic factor is the main reason for land use/land cover (LULC) and landscape change on a global scale [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, understanding change processes of landscape and influencing factors, namely biophysical and anthropogenic, has become a priority for researchers, managers, and decision makers [4][5][6][7]. In this regard, population growth as an anthropogenic factor is the main reason for land use/land cover (LULC) and landscape change on a global scale [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ayre et al [32] developed procedures that incorporate landscape features into the environmental management process and present a conceptual foundation for incorporating landscape ecology into the risk assessment process. Krajewski et al [33] based on the map data of 140 years (1863-2013), using a landscape change index to analyze driving forces of forest resources change and forest transformation in a landscape park, and provided a theoretical and practical guidance for the protection of regional forest landscape resources. This kind of research also showed that the landscape change index was used as a way of monitoring landscape changes and therefore could be used for landscape ecological risk assessment [34].…”
Section: Introductionmentioning
confidence: 99%
“…It cannot explain the quality of population urbanization. The population is an important driving force to accelerate urban landscape change, especially to expand built-up areas [14]. At present, the impact of the household registration system on population urbanization cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous spread of cities, high-quality arable land is being lost and fragmentation landscape patterns are increasing, thereby posing threats to sustainable development and regional food security [13]. The change in population size and land use policy in urbanization are important driving forces for the forest spatial changing pattern, which affects the changes in the regional landscape [14]. Hence, urban development must focus on the use of comprehensive resources, handle the coordinated development of population and land urbanization properly, promote a new type of urbanization, and realize the sustainability of urban modernization [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation